Hybridization between two parapatric ranid frog species in the northern Sierra Nevada, California, USA. Issue 20 (4th October 2019) - Peek, Ryan A.; Bedwell, Mallory; O'Rourke, Sean M.; Goldberg, Caren; Wengert, Greta M.; Miller, Michael R.
Abstract: Contact zones between species provide a unique opportunity to test whether taxa can hybridize or not. Cross‐breeding or hybridization between closely related taxa can promote gene flow (introgression) between species, adaptation, or even speciation. Though hybridization events may be short‐lived and difficult to detect in the field, genetic data can provide information about the level of introgression between closely related taxa. Hybridization can promote introgression between species, which may be an important evolutionary mechanism for either homogenization (reversing initial divergence between species) or reproductive isolation (potentially leading to speciation). Here, we used thousands of genetic markers from nuclear DNA to detect hybridization between two parapatric frog species ( Rana boylii and Rana sierrae ) in the Sierra Nevada of California. Based on principal components analysis, admixture, and analysis of heterozygosity at species diagnostic SNPs, we detected two F1 hybrid individuals in the Feather River basin, as well as a weak signal of introgression and gene flow between the frog species compared with frog populations from two other adjacent watersheds. This study provides the first documentation of hybridization and introgression between these two species, which are of conservation concern.